Developing an Alternative Tourism in Buleleng: Needs Based Education and Public Capital - Andiani, Nyoman Dini; Widiastini, Ni Made Ary (Universitas Pendidikan Ganesha, 2017)
Penelitian This research was conducted in order to understand a form of education that is based on the needs of the community through the use of a variety of capital that can be used in the development of tourism in Buleleng. This study uses ethnographic approach which is a culturalist approach and its emphasis on peoples lives. This approach is used considering the culture comes from the community and maintained and implemented by the community. Data in this study were collected through observation and interviews. Moreover carried out literature to books, previous studies and articles that have relevance to the case examined in this study. The data processing is done qualitative descriptive narrative presented. In this case, the existence of regional capitals in Buleleng are very interesting to be known, understood and analyzed in depth in order to produce a model of sustainable tourism. The development of an area into a tourist attraction is not an easy matter. However, the government can work together with local communities to develop the existing tourism in the area, where the first step can be done by utilizing local labor in the area and to synergy between the needs of the community with programs implemented so that the common goal of improving the quality of tourism and social welfare can be achieved.Keywords: an alternativeÂ , education, tourism